Políticas públicas e agricultura familiar na fronteira oeste do Rio Grande do Sul: o PRONAF em São Borja (2014-2017) - (:unkn) unknown (Universidade Federal do Pampa, 2019)
The socioeconomic investment, private or public, focused on family agriculture is essential for the promotion of rural development that is economically viable, socially fair and environmentally correct. In this sense, it is essential to the role played by public policies, as is the case, for example, the Programa Nacional de Fortalecimento da Agricultura Familiar – PRONAF. This work consists in the analysis of the implementation of this public policy in the region of the western frontier gaucho, with special focus on municipality of the São Borja, which is taken by a number of factors, as representative of the region under analysis. This project relied on the analysis of data concerning the amounts of contracts and contractors, as well as with the continuous monitoring and the collection of information from both the actual and potential beneficiaries of the program regarding street bureaucrats – implementers for excellence of this policy. Among the main findings, it can be noted that the implementation of the program in the region, although not severely hampered is less influenced by some factors of macroeconomic nature, which refer to the existence of situations and priorities, particularly with respect to the beneficiary of the program, which differ from other regions of Rio Grande do Sul and even of the country (without, however, must also submit certain similarities). In fact, rural credit made available through the PRONAF enables beneficiaries the development of farming activities at household level (which would be seriously compromised without the existence of the program); however, given the regional socioeconomic situation, their effects tend to be minimized in the medium and long term, which demonstrates the need to rethink their implementation based especially on two fronts: greater publicity of rules and benefits of PRONAF and the social value of economic-financial investment represented by rural credit for the small farmer.
Keywords: Agricultura familiar; Política pública; Desenvolvimento rural; Programa Nacional de Fortalecimento da Agricultura Familiar (Brasil); São Borja, RS; Family Farming; Public policy; CNPQ::CIENCIAS HUMANAS